Mitigation of Magnetic Field under Double-Circuit 220kV Overhead Transmission Line - Osama Elsayed Gouda; Adel Z. El Dein (Institute of Advanced Engineering and Science, 2012)
This paper studies the effect of various mitigation loop configurations namely: single horizontal mitigation loop (two conductors), two separate horizontal mitigation loops (four conductors) and single vertical mitigation loop (two conductors), on the magnetic field produced by 220kV double-circuit overhead transmission line. Also, in this paper a further reduction in the magnetic field is achieved by inserting properly-selected capacitors within these mitigation loops. The obtained results indicate that the reduction in the magnetic field by using these mitigation loops largely depends on the arrangements and the locations of these loops with respect to the conductors of 220kV double-circuit overhead transmission line. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1521